The Impact of iron tablet administration and nutritional counseling: Hemoglobin level improvement in anemic pregnant women - Yurnila; Helmizar; Lipoeto, Nur Indrawaty (Public Health Risk Assesment Journal, 2024)
Objective: According to the 2013 Riskesdas, the prevalence of anemia in Indonesia was 37.1%. Data from the Pariaman City Health Office showed that the prevalence of anemia in 2014 was 43.1%. This study aims to determine the effect of iron (Fe) tablets and nutritional counseling on hemoglobin levels in pregnant women with anemia in the Pariaman City area in 2016. Methods: This study is a quantitative study using a quasi-experimental design. The study population consisted of third-trimester pregnant women with anemia, divided into two groups: the Fe tablet group (n=20) and the Fe tablet plus nutritional counseling group (n=20). Data analysis was performed using univariate and bivariate analysis with the Dependent T-Test statistical test. Results: The results showed that the average knowledge score in the Fe group was 0.3, while in the Fe plus nutritional counseling group it was 1.4. The average change in knowledge scores between the two groups showed a significant increase (p=0.002). The average attitude score in the Fe group was 2.15, while in the Fe plus nutritional counseling group it was 2.75. The average change in attitude scores between the two groups was not significant (p=0.205). The average action score in the Fe group was 1.050, while in the Fe plus nutritional counseling group it was 2.7. The average change in action scores between the two groups showed a significant increase (p=0.002). The average difference in hemoglobin levels in the Fe group was 0.280, while in the Fe plus nutritional counseling group it was 0.690. The average change in hemoglobin levels between the two groups showed a significant increase (p=0.008). Conclusion: It can be concluded that the provision of Fe supplementation and nutritional counseling results in a higher increase in hemoglobin levels compared to Fe tablets alone. It is hoped that nutritionists in the field will be more active in providing nutritional counseling to pregnant women with anemia to increase their knowledge about anemia. Novelty/Originality of this article: This study proposes an integrated nutritional intervention model combining Fe tablets with a community-based interactive nutritional counselling program. This model can increase the effectiveness of anaemia control programs in pregnant women by combining supplementation and education.